Exosomes as drug delivery system in gastrointestinal cancer - Xie, Fangyuan; Huang, Yueying; Zhan, Yangyang; Bao, Leilei (Frontiers in Oncology, 2023)
Gastrointestinal cancer is one of the most common malignant tumors, among which the incidence and mortality of gastric cancer, liver cancer, colorectal cancer, and pancreatic cancer are relatively high. Exosomes are extracellular vesicles with a diameter of 40-100 nm, secreted by various cells and widely distributed in body fluids. They are natural endogenous nanocarriers with low immunogenicity, high biocompatibility, and natural targeting, and can transport lipids, proteins, DNA, and RNA. Exosomes are rich in proteins, nucleic acids, lipids, and other bioactive components, which can play a role in information transmission and regulation of cellular physiological and pathological processes during the progression of gastrointestinal cancer. In this paper, the role of exosomes in gastrointestinal cancers is briefly reviewed, with emphasis on the application of exosomes as drug delivery systems for gastrointestinal cancers. Finally, the challenges faced by exosome-based drug delivery systems are discussed.